2017
DOI: 10.21831/pg.v12i1.14055
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan bahan ajar geometri SMP berbasis cognitive load theory berorientasi pada prestasi belajar siswa

Abstract: Penelitian ini bertujuan untuk menghasilkan bahan ajar geometri SMP berbasis Cognitive Load Theory (CLT) serta mendeskripsikan kualitas kevalidan, kepraktisan dan keefektifan bahan ajar tersebut. Bahan ajar yang dikembangkan berupa buku pengayaan geometri untuk SMP kelas VII dan VIII sesuai dengan Kurikulum 2006. Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan model penelitian desain dari Plomp yang terdiri atas tiga tahap: preliminary research, prototyping phase, dan assessment phase. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
4
0
6
Order By: Relevance
“…The results of this study are similar to the results of research conducted by the research (Prasetyo, 2018). (Sidarta and Yunianta, 2017), (Salafudin et al, 2018), (Pangesti and Retnowati, 2017), (Rizal and Hernawati, 2017), (Ningrum and Mariono, 2016), (Listiani and Prihatnani, 2018). The results of the study concluded that the media created had the positive impact on students' interests and learning outcomes.…”
Section: Methodsmentioning
confidence: 90%
“…The results of this study are similar to the results of research conducted by the research (Prasetyo, 2018). (Sidarta and Yunianta, 2017), (Salafudin et al, 2018), (Pangesti and Retnowati, 2017), (Rizal and Hernawati, 2017), (Ningrum and Mariono, 2016), (Listiani and Prihatnani, 2018). The results of the study concluded that the media created had the positive impact on students' interests and learning outcomes.…”
Section: Methodsmentioning
confidence: 90%
“…The steps used to provide the questionnaire criteria for the practicality of teaching materials are as follows (Pangesti, & Retnowati, 2017):…”
Section: Analysis Of Student Questionnairesmentioning
confidence: 99%
“…a. recap the total score from the practicality sheet that the students had filled in for each statement b. calculate the average score of each statement from the practicality questionnaire sheet that has been filled in by students, with the formula = ∑ ℎ c. questionnaire criteria for the practicality of teaching materials Teaching materials are said to meet the practical aspect if the minimum average assessment is in the "Good" criteria (Pangesti & Retnowati, 2017). In this stage, the researcher analyzed several things to provide an overview of the developed teaching materials.…”
Section: Analysis Of Student Questionnairesmentioning
confidence: 99%
“…Kondisi ini jelas menunjukkan bahwa bahan ajar yang dimiliki oleh guru di sekolah tersebut masih belum memadai. Hal tersebut sesuai dengan temuan beberapa peneliti lainnya (misalnya Gazali, 2016;Pangesti & Retnowati, 2017), yang memperkuat adanya indikasi bahwa bahan ajar yang dimiliki oleh guru matematika saat ini kurang relevan dengan kebutuhan belajar siswa saat ini.…”
Section: Pendahuluanunclassified